(untitled) (Marketing Journal, 2025)
This paper examines the role of innovative marketing in advancing the green economy through integration with sustainability principles and measurable impact. The study identifies key theories such as the Triple Bottom Line, Diffusion of Innovations, and Stakeholder Theory, linking them to purpose-driven branding and circular business models. Special attention is given to Uzbekistan’s green transition policies, renewable energy projects, and financial mechanisms supporting low-carbon development. The findings suggest that marketing becomes a strategic instrument for sustainable transformation when embedded in verified impact systems and aligned with policy and finance frameworks.